The Relationship between Personal Hygiene and the Incidence of Scabies Disease in Students at Al-Adabiy Islamic Boarding School, Pontianak - Putri, Nurfaidah Sulistiningtyas Sugirah; Rahmayanti, Rahmayanti; Rialita, Ambar (PSPP JOURNALS, 2024)
Scabies is a skin disease that is influenced by the environment and personal hygiene. Caused by infestation and sensitization of Sarcoptes scabiei var. hominis. Symptoms of scabies are complaints of itching at night, with clinical signs of papules or vesicles, the peak is like a tunnel in the predilection area, grayish white, straight or curved. The objective of this study was to determine the relationship between personal hygiene and the incidence of scabies in students at the Al-Adabiy Pontianak Islamic Boarding School in 2023. The research design used in this study was observational analytic with a cross-sectional approach conducted on 60 students of Al-Adabiy Islamic Boarding School using a simple random sampling technique, hypothesis testing using Fisher's test. The results showed that respondents who had scabies were in the age range of 12-16 years (65%), were in class X (50%) and were dominated by males (60%). 85% of students had poor personal hygiene with a scabies incidence rate of 33.3%. The results of the Fisher's test obtained a significance value (sig.) of 0.023 (p <0.05). There is a relationship between personal hygiene and the incidence of scabies.